2010
DOI: 10.3324/haematol.2010.021923
|View full text |Cite
|
Sign up to set email alerts
|

Similar hypercoagulable state and thrombosis risk in type I and type III protein S-deficient individuals from families with mixed type I/III protein S deficiency

Abstract: The online version of this article has a Supplementary Appendix. BackgroundProtein S, which circulates in plasma in both free and bound forms, is an anticoagulant protein that stimulates activated protein C and tissue factor pathway inhibitor. Hereditary type I protein S deficiency (low total and low free protein S) is a well-established risk factor for venous thrombosis, whereas the thrombosis risk associated with type III deficiency (normal total and low free protein S) has been questioned. Design and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 51 publications
3
50
1
1
Order By: Relevance
“…system has accumulated through a series of clinical studies demonstrating that the plasma TFPIa concentration and anticoagulant activity are decreased in PS-deficient plasma, suggesting that PS and TFPIa circulate as a complex in plasma. [111][112][113] Functional studies of the TFPIa-PS interaction have revealed that it requires K3 residues Arg199 8 and Glu226 114 and the presence of a membrane surface. 6 Thus, it appears that PS enhances FXa inhibition primarily by localizing TFPIa to the membrane surface, a notion supported by experiments demonstrating that PS has cofactor activity toward the soluble TFPI variant protein K1K2K3 8,115 but has no cofactor activity toward the same variant protein when it is attached to the cell surface with a GPI anchor.…”
Section: Inhibition Of Fxa By Tfpia and Tfpibmentioning
confidence: 99%
“…system has accumulated through a series of clinical studies demonstrating that the plasma TFPIa concentration and anticoagulant activity are decreased in PS-deficient plasma, suggesting that PS and TFPIa circulate as a complex in plasma. [111][112][113] Functional studies of the TFPIa-PS interaction have revealed that it requires K3 residues Arg199 8 and Glu226 114 and the presence of a membrane surface. 6 Thus, it appears that PS enhances FXa inhibition primarily by localizing TFPIa to the membrane surface, a notion supported by experiments demonstrating that PS has cofactor activity toward the soluble TFPI variant protein K1K2K3 8,115 but has no cofactor activity toward the same variant protein when it is attached to the cell surface with a GPI anchor.…”
Section: Inhibition Of Fxa By Tfpia and Tfpibmentioning
confidence: 99%
“…3,4 Hereditary protein S deficiency is a haploinsufficiency disorder associated with an increased risk of venous thrombosis. 5 Protein S deficiency can be classified as type I (decreased levels of both total and free protein S antigen), type II (decreased activated protein C-cofactor activity but total and free protein S antigen levels within their normal ranges), and type III (decreased levels of free protein S antigen levels only). 6 The genetic basis of protein S deficiency is heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…8 We, along with others, have shown that gross deletions and insertions of PROS1 are present in approximately 30% of the point mutation-negative families. 5,10,11 Most of the insights regarding the association between protein S deficiency and venous thrombosis have been derived from studies of thrombophilic families. This has led to the notion that the risk of venous thrombosis in protein S deficient subjects is 5 to 10 times higher than in nonprotein S deficient relatives.…”
Section: Introductionmentioning
confidence: 99%
“…ЭТП повышен практически при любых видах тромбофилии, включая полиморфизм G20210A [32], дефицит антитромбина [33], V Leiden [34] (с добавле-нием aPC), дефицит протеина S [35] (с добавлением aPC), а также при приеме оральных контрацептивов (с добавлением aPC) [36] и онкологических заболева-ниях [37]. В работах [38,39] ЭТП был повышен при бе-ременности, но в [40] ЭТП возрастал в I триместре относительно нормы и далее держался постоянным в течение всего срока беременности, в то время как маркеры активации свертывания D-димеры, F1 + 2 и TAT возрастали.…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified